PILIHAN RASIONAL MERANTAU UNTUK KESEJAHTERAAN KELUARGA DI DESA SENGANAN, KECAMATAN PENEBEL, KABUPATEN TABANAN (JURNAL ILMIAH SOSIOLOGI: SOROT, 2023)
Merantau means a movement of people from their place of origin to another area, but with their own will aims to make a living, study, or seek experience. This research uses a qualitative approach with explanatory descriptive type. James S. Coleman's rational choice theory is used as a scalpel to analyze people's choices for migrating and the benefits of migrating for the people of Senganan Village. The people of Senganan Village make their choice to migrate by considering the pull and push factors from the area where they come from and where they want to migrate, and carry out their customary obligations by means to provide religious service. It was concluded that migrating has benefits from various aspects, namely economic, social, cultural and educational aspects, and aims to improve family welfare. It is recommended that families who are already prosperous contribute more to building Senganan village.